C‐ITS road‐side unit deployment on highways with ITS road‐side systems: A techno‐economic approach. Issue 7 (7th May 2021) - Degrande, Thibault; Van den Eynde, Simon; Vannieuwenborg, Frederic; Colle, Didier; Verbrugge, Sofie
Abstract: Connectivity and cooperation are considered important prerequisites to automated driving, as they are crucial elements in increasing the safety of future automated vehicles and their full integration in the overall transport system. Although many European Member States, as part of the C‐Roads Platform, have implemented and are still implementing Road‐side Units (RSUs) for Cooperative Intelligent Transportation Systems (C‐ITS) within pilot deployment projects, the platform aspires a wide extension of deployments in the coming years. Therefore, this paper investigates techno‐economic aspects of C‐ITS RSU deployments from a road authority viewpoint. A two‐phased approach is used, in which firstly the optimal RSU locations are determined, taking into account existing road‐side infrastructure. Secondly, a cost model translates the amount of RSUs into financial results. It was found that traffic density has a significant impact on required RSU density, hence impacting costs. Furthermore, major cost saving can be obtained by leveraging existing road‐side infrastructure. The proposed methodology is valuable for other member states, and in general, to any other country aspiring to roll out C‐ITS road infrastructure. Results can be used to estimate required investment costs based on legacy infrastructure, as well as to benchmark with the envisioned benefits from the deployed C‐ITS services.